Preparation and Application of Lignin‐Based Epoxy Resin from Pulping Black Liquor. Issue 12 (24th March 2020) - Zhu, Yanchao; Li, Zheng; Wang, Xiaofeng; Ding, Na; Tian, Yumei
Abstract: In the present work, lignin was isolated from pulping black liquor. Selective precipitation was achieved by adding hydrochloricacid to adjust pulping black liquor pH from 1 to 5. Reaction pH, reaction temperature and the content of lignin were investigated in the total process. A considerable increase in the amount of precipitate was observed while pH was decreasing. Lignin obtained from pulping black liquor had been used as the reactant to partly replace bisphenol A in preparing epoxy resins with different lignin additives at 90 °C. The mechanical and the thermal properties of cured lignin‐based epoxy resins were compared with those at different contents of lignin and reaction temperatures with ethylenediamine as the curing agent. The cured lignin‐based epoxy resins with 20 wt. % lignin at 90 °C showed the highest viscosity up to 396 MPa⋅s. We had successfully got good performance lignin‐based epoxy resin. Abstract : Lignin was obtained by adding hydrochloric acid to adjust pulping black liquor pH from 1 to 5 and used as the reactant to partly replace bisphenol A in the synthesis of lignin‐based epoxy resin at 90 °C. The mechanical and the thermal properties of cured lignin‐based epoxy resins were compared with those at different contents of lignin and reaction temperatures.